METODE PELAKSANAAN DAN ANALISA BIAYA BEKISTING PADA PEKERJAAN STRUKTUR (STUDI KASUS : PEMBANGUNAN GEDUNG ASTRA HONDA MOTOR SEMARANG) - Budi Rohmad Wijayanto; M. Yudi Purnawan; Sukamta Sukamta; Arif Hidayat (Jurnal Karya Teknik Sipil, 2014)
The analysis of management constructionin the implementation of development projectsneeds to be done in order to obtain an effective construction methods and cost efficient.The purpose of this study is to compare two methods of formwork on each floor plate to get a more feasible method applied is based on the time and cost of the project. Stages in conducting the study are:Calculation of the volume of work on projects that include foundation work, tie beams, columns, beams, plates, ladder, shearwall, GWT (Ground Water Tank). Cost calculation on project work, in order to get the cost for all elements of the building structure. Calculation of the power plate and beams in project work, for the purposes of dismantling formwork manually, with estimate the time of the plate and beam formwork to release. Comparison of two implementation methods of calculation of the work on the first fabrication of formwork plate method done at the beginning of the three floors, while the second method of fabrication of formwork is onlydone at the beginning of the two floors. Comparison of plate work and the work done by the time and the project costs (direct and indirect costs). Implementation of management analysis performed in order to obtain an effectiveconstruction methods and cost efficient, so the comparison of the results of both methods can be concluded that the second method is more efficient and can be applied to the implementation of the project, with the difference in cost Rp.277 288 777, - and the difference in duration of work is 5 days longer.